Identification of Genes Related to Paulownia Witches’ Broom by AFLP and MSAP - Cao, Xibing (MDPI, 2014)
DNA methylation is believed to play important roles in regulating gene expression in plant growth and development. Paulownia witches’ broom (PaWB) infection has been reported to be related to gene expression changes in paulownia plantlets. To determine whether DNA methylation is associated with gene expression changes in response to phytoplasma, we investigated variations in genomic DNA sequence and methylation in PaWB plantlets treated with methyl methane sulfonate (MMS) using amplified fragment length polymorphism (AFLP) and methylation-sensitive amplification polymorphism (MSAP) techniques, respectively. The results indicated that PaWB seedings recovered a normal morphology after treatment with more than 15 mg·L(−1) MMS. PaWB infection did not cause changes of the paulownia DNA sequence at the AFLP level; However, DNA methylation levels and patterns were altered. Quantitative real-time PCR (qRT-PCR) showed that three of the methylated genes were up-regulated and three were down-regulated in the MMS-treated PaWB plantlets that had regained healthy morphology. These six genes might be involved in transcriptional regulation, plant defense, signal transduction and energy. The possible roles of these genes in PaWB are discussed. The results showed that changes of DNA methylation altered gene expression levels, and that MSAP might help identify genes related to PaWB.